Kiprah Pesantren dalam Pembangunan Nasional - Siddik, Hasbi (Al-Riwayah : Jurnal Kependidikan, 2017)
Islamic boarding school is the forerunner of Islamic education in Indonesia, which was founded due to the demands and needs of the times. Pesantren is born because of a sense of obligation Islamic da’wah, and disseminating the teachings of Islam as well as develop cadres ulama and da’i. Islamic boarding schools have long been an institution that has an important contribution to the nation to participate. A large number of pesantren in Indonesia, as well as a very large number of students at each boarding makes this institution to be reckoned with in terms of nation-building in education and moral. Improvements are continually made to the schools, both in terms of management, academic (curriculum) and facilities, making the boarding out of the traditional and conservative impression that had been assumed. The origin comes from the Hindu tradition schools that have long grown in this country. While the opinions of others say that the origin of the system of boarding education is a growing tradition in the Islamic and Arab world itself. Education schools have two teaching systems, i.e. systems sorogan, often called the individual systems, and systems or wetonan bandongan often called collectively. Boarding schools are educational institutions that grow and thrive in the midst of the community, its existence has been recognized by the community